Analysis and Evaluation of Short City Tunnel Lighting Solutions - Vytenis Puzonas; Alfredas Laurinavičius; Lina Juknevičiūtė-Žilinskienė (The Baltic Journal of Road and Bridge Engineering)
The study focused on the lighting in road tunnels within the city of Vilnius. The condition of the lighting was assessed both visually and through measurements of road surface illumination (brightness). High-quality lighting in road tunnels is crucial for ensuring safe and optimal conditions for car travel. Well-designed lighting reduces stress, enhances information visibility for drivers, ensures uniform visibility throughout the tunnel, and promotes efficient energy use. After analysing the data, the required road surface luminance was calculated following the technical regulations applicable to road tunnel lighting design in other countries. The results suggest a need to update the lighting in existing road tunnels by adopting new types of lamps, adjusting their arrangement, and enhancing the physical characteristics of the tunnels.